Redefining the Philosophy of Mikul Dhuwur Mendhem Jero in Elderly Care in Rural Java - Triratnawati, Atik; Budi Winarni, Yohana (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
Modernization has shifted the meaning of the philosophy of mikul dhuwur mendhem jero or filial piety of children caring for parents or the elderly in rural Java. Changes in family structure have led to fewer children being able to care for their parents, although the value of filial piety remains in the hearts of children. It is important to explore the shift in meaning in local wisdom-based elderly care mechanisms in the context of modernization. This article aims to describe the importance of redefining the Javanese philosophy of parental care due to changes in family structure and relationship patterns.  The research used qualitative approach. The study was conducted in Bantul, Yogyakarta between May and July 2023. There eight informants involve in this study who are either elderly or caregivers. Data was collected using in-depth interview and observation. The findings show that even though there are four pattern of elderly care (family care, paid care, self-care, and social care), family care is still favor by members of the family. Material becomes a benchmark for the level of devotion to parents that they recognize together, and the role of social mechanisms is still running well, although limited. The level of filial piety of children to their parents is reflected in the quality of care and how well they pay attention. This research emphasizes the adaptation of traditional values to modern realities while maintaining the essence of children's filial responsibilities in the Javanese cultural context.